Shocking violence : youth perpetrators and victims--a multidisciplinary perspective - Moser, Rosemarie Scolaro; Frantz, Corinne E. (Charles C Thomas, 2000)
Shocking Violence: Youth Perpetrators and Victims, A Multidisciplinary Perspective is written by contributors in the diverse fields of psychology, social work, educations, law enforcement, ministry, and the judicial system. The chapters cover the topic of youth violence with emphasis on recommendations for educators, parents, and treatment professionals to help children at risk. Many factors that contribute to youth violence are explored including an examination of personality development by Corrine Frantz and Rosemarie Scolaro Moser, who cite the incidents at Pearl, Mississippi, Jonesboro, Ar.